Osing Culture Conservation in Perspective Corporate Social Responsibility - Ratna Wijayanti Daniar Paramita; Noviansyah Rizal; Muchamad Taufiq; Muhaimin Dimyati (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
This research is a qualitative research that uses an ethnomethodology approach to study the preservation of Osing culture in Banyuwangi in academic texts. At present, the Government of Banyuwangi packs a variety of indigenous cultures and cultures in an event known as Banyuwangi Festival, an event that invites both domestic and foreign audiences. Meanwhile, cultural actors with all the limitations of their funds are trying to maintain the indigenous culture that has taken root in their village by establishing a cultural studio that is funded independently. Local companies have mostly channeled social responsibility funds but not in the form of social culture. The results of this study which was also the result of the Focus Discussion Group (FGD) forum were agreed that local companies would channel cultural CSR funds by providing direct guidance to cultural actors or cultural studio owners. As the implementation of the policy, the agreement is then stated in the academic text sheet.